Impact of Frailty on Clinical Outcomes in Patients With Critical Limb Ischemia. (July 2018) - Takeji, Yasuaki; Yamaji, Kyohei; Tomoi, Yusuke; Okazaki, Jin; Tanaka, Kiyoshi; Nagae, Ayumu; Jinnouchi, Hiroyuki; Hiramori, Seiichi; Soga, Yoshimitsu; Ando, Kenji
Abstract : Background: The predictive ability of patient frailty on clinical outcomes after revascularization in patients with critical limb ischemia remains largely unknown. Methods and Results: We enrolled 643 patients with critical limb ischemia treated with endovascular therapy (N=486) or bypass surgery (N=157) in January 2010 to January 2016, and prospectively assessed them using a 9-level clinical frailty scale (CFS). Patients were divided into 3 groups according to CFS levels: low (CFS level, 1–3; N=234), intermediate (CFS level, 4–6; N=196), and high (CFS level, 7–9; N=213) groups. Clinical follow-up rate was 95.8% at 2 years. In the low, intermediate, and high CFS groups, 2-year overall survival rates were 80.5%, 63.1%, and 49.3% ( P <0.001) and amputation-free survival rates were 77.9%, 60.5%, and 46.2% ( P <0.001), respectively. In multivariable analysis, higher frailty was independently associated with all-cause death (intermediate CFS group: adjusted hazard ratio, 1.64; 95% confidence interval, 1.12–2.42; P =0.01; high CFS group: adjusted hazard ratio, 2.22; 95% confidence interval, 1.52–3.23; P <0.001) and a composite of all-cause death and major amputation (intermediate CFS group: adjusted hazard ratio, 1.72; 95% confidence interval, 1.19–2.48; P =0.004; high CFS group: adjusted hazard ratio, 2.34; 95% confidence interval, 1.64–3.35; P <0.001). Frailty was also independently associated with overall survival and amputation-free survival in patients aged ⩽75 and >75 years, those who underwent endovascular therapy or bypass surgery, and those with or without chronic renal failure, without significant interactions. Conclusions: Frailty was independently associated with 2-year overall survival and amputation-free survival in patients with critical limb ischemia treated with revascularization, irrespective of age, revascularization mode, and chronic renal failure status. Abstract : Supplemental Digital Content is available in the text.